Pemodelan Toko Tiga Dimensi Menggunakan Augamented Reality Berbasis Android - Natalia Arum Prastiwi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The INKOPAU Jakarta Marketing Office is a marketing office whose marketing process is still done manually by coming directly to marketed revivals, so the marketing process takes a long time, the process of explaining building information is still done manually, namely explaining directly to prospective buyers, so the risk of errors in conveying information. This study aims to create an android based three-dimensional building application at the INKOPAU Marketing Office with the MDLC (Multimedia Development Life Cycle) application development method. The tools used for developing this application use Blender 3D and Unity to implement Augmented Reality, testing this application using black-box-testing. The result of this research is that the application can facilitate the marketing department in marketing and explaining buildings in the INKOPAU Marketing Office